An IL-4/21 Inverted Cytokine Receptor Improving CAR-T Cell Potency in Immunosuppressive Solid-Tumor Microenvironment - Wang, Yi; Jiang, Hua; Luo, Hong; Sun, Yansha; Shi, Bizhi; Sun, Ruixin; Li, Zonghai (Frontiers in Immunology, 2019)
Incorporation of inverted cytokine receptor (ICR) such as interleukin (IL)-4 vs. IL-7 (4/7) ICR is one strategy to improve the antitumor activities of chimeric antigen receptor (CAR) modified T (CAR-T) cells facing immunosuppressive cytokines. Here we report a novel interleukin (IL)-4 vs. IL-21 ICR (4/21 ICR) that enhanced CAR-T cell potency in IL-4+ tumor milieu via a different working-mechanism from 4/7 ICR. Upon IL-4 stimulation, 4/21 ICR activated the STAT3 pathway and promoted Th17-like polarization and tumor-targeted cytotoxicity in CAR-T cells in vitro. Furthermore, 4/21 ICR-CAR T cells persisted and eradicated established IL-4+ tumors in vivo. Thus, 4/21 ICR is a promising clinical CAR-T cell therapeutics for solid tumors rich in IL-4.